2006
DOI: 10.1242/dev.02357
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling establishes anteroposterior neuronal polarity and requires retromer inC. elegans

Abstract: Secreted Wnt proteins influence neural connectivity by regulating axon guidance, dendritic morphogenesis and synapse formation. We report a new role for Wnt and Frizzled proteins in establishing the anteroposterior polarity of the mechanosensory neurons ALM and PLM in C. elegans. Disruption of Wnt signaling leads to a complete inversion of ALM and PLM polarity: the anterior process adopts the length, branching pattern and synaptic properties of the wild-type posterior process, and vice versa. Different but ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(232 citation statements)
references
References 48 publications
9
217
0
6
Order By: Relevance
“…Wnts function in several developmental processes along the anterior-posterior axis during larval development, functioning in cell-fate specification, neuronal migration, and neuronal cell polarity (Eisenmann 2005). For several of these larval Wnt-dependent processes, the Wnt genes also display functional redundancy, such that strong phenotypes are only apparent when multiple Wnt genes are mutated (Zinovyeva and Forrester 2005;Gleason et al 2006;Hilliard and Bargmann 2006;Pan et al 2006;Prasad and Clark 2006;Green et al 2008;Yamamoto et al 2011). This indicates that while in some C. elegans processes, distinct Wnt and Wnt receptor pairings may be used; in other processes, the identity of individual Wnts may not be as important as the reception of a threshold amount of Wnt signal.…”
Section: Wnt Pathway Components In C Elegansmentioning
confidence: 99%
“…Wnts function in several developmental processes along the anterior-posterior axis during larval development, functioning in cell-fate specification, neuronal migration, and neuronal cell polarity (Eisenmann 2005). For several of these larval Wnt-dependent processes, the Wnt genes also display functional redundancy, such that strong phenotypes are only apparent when multiple Wnt genes are mutated (Zinovyeva and Forrester 2005;Gleason et al 2006;Hilliard and Bargmann 2006;Pan et al 2006;Prasad and Clark 2006;Green et al 2008;Yamamoto et al 2011). This indicates that while in some C. elegans processes, distinct Wnt and Wnt receptor pairings may be used; in other processes, the identity of individual Wnts may not be as important as the reception of a threshold amount of Wnt signal.…”
Section: Wnt Pathway Components In C Elegansmentioning
confidence: 99%
“…In yeast, a cluster of proteins termed the retromer complex directs endosome-to-Golgi retrieval of proteins and in vertebrate systems the retromer complex functions in basal-to-apical transcytosis (Verges et al, 2004). Recently, two groups have independently shown that the C. elegans ortholog of the yeast retromer complex subunit Vps35p is required for the long-range signaling capabilities of Egl-20 (C. elegans Wnt ortholog) (Coudreuse et al, 2006;Prasad and Clark, 2006). Mutation in vps35 leads to defects in Wnt-mediated posterior lateral microtubule (PLM) mechanosensory neuron polarity as well as Q neuroblast migration.…”
Section: Wnt Extracellular Transportmentioning
confidence: 99%
“…In addition, when retromer function is abolished by vps-26-and vps-35-null mutations, the mutant phenotype appears less severe than Wnt-null mutants suggesting that not all of the signaling functions of C. elegans Wnts (i.e. short-range) are impaired (Prasad and Clark, 2006).…”
Section: Wnt Extracellular Transportmentioning
confidence: 99%
“…Le retromer a été initialement identifié chez la levure comme étant requis pour le routage intracellulaire des hydrolases vacuolaires [17]. Chez le nématode, la perte de fonction du retromer induit des phénotypes restreints observables dans la partie postérieure de l'animal, et similaires à ceux qu'entraîne une altération de la voie de signalisation WNT [14,19]. On observe notamment une inversion de polarité dans la migration antéro-postérieure de certains neurones [14] et l'extension asymétrique de prolongements neuronaux [19].…”
Section: Wntless Et Le Retromer Sont Requis Pour La Signalisation Wntunclassified
“…Chez le nématode, la perte de fonction du retromer induit des phénotypes restreints observables dans la partie postérieure de l'animal, et similaires à ceux qu'entraîne une altération de la voie de signalisation WNT [14,19]. On observe notamment une inversion de polarité dans la migration antéro-postérieure de certains neurones [14] et l'extension asymétrique de prolongements neuronaux [19]. Des études de mosaïcisme (voir Glossaire) ont montré que le retromer était spécifiquement requis dans les cellules qui sécrètent WNT.…”
Section: Wntless Et Le Retromer Sont Requis Pour La Signalisation Wntunclassified